Research Progress and Exploration on Standardized Surgical Procedures for Colorectal Cancer - Kaiyuan JI; Weixing ZHANG; Lingxiao WANG; Yifan KANG; Yaoping LI (Zhongliu Fangzhi Yanjiu)
The advancement of medical technology has led to significant progress in the research of standardized surgical procedures for colorectal cancer, resulting in enhanced treatment regimens from preoperative to postoperative stages. Standardized surgical procedures are crucial for improving patient survival rates, reducing recurrence rates, minimizing complications, and improving quality of life. This article summarizes the latest research results on the classification, surgical methods, and adjuvant therapy of colorectal cancer surgery; analyzes and explores standardized surgical treatment strategies; and aims to provide reference and guidance for the clinical management of colorectal cancer.